2022
DOI: 10.1111/gcb.16545
|View full text |Cite
|
Sign up to set email alerts
|

Global warming is increasing the discrepancy between green (actual) and thermal (potential) seasons of temperate trees

Abstract: Over the past decades, global warming has led to a lengthening of the time window during which temperatures remain favorable for carbon assimilation and tree growth, resulting in a lengthening of the green season. The extent to which forest green seasons have tracked the lengthening of this favorable period under climate warming, however, has not been quantified to date. Here, we used remote sensing data and long-term ground observations of leaf-out and coloration for six dominant species of European trees at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…For 108 forests across eastern North America, dendrometers indicated an earlier start of the season in warmer springs (beginning of tree ring formation), but no effect on annual increment (Dow et al, 2022). A study across 1773 sites in central Europe found that the 'green season' (a phenological season) lags significantly behind the prolonging of the thermal season (T-threshold of 5 °C; Fu et al, 2022). Yet, in the Harvard forest, a longer and warmer meteorological season (1992-2015) revealed a significant increase of NEP (based on eddy covariance data) in this relatively young forest, explained by enhanced growth above, but not below the ground (Finzi et al, 2020).…”
Section: T H E Grow I Ng Se a Son I N A C L I M At E C H A Nge Con T ...mentioning
confidence: 99%
“…For 108 forests across eastern North America, dendrometers indicated an earlier start of the season in warmer springs (beginning of tree ring formation), but no effect on annual increment (Dow et al, 2022). A study across 1773 sites in central Europe found that the 'green season' (a phenological season) lags significantly behind the prolonging of the thermal season (T-threshold of 5 °C; Fu et al, 2022). Yet, in the Harvard forest, a longer and warmer meteorological season (1992-2015) revealed a significant increase of NEP (based on eddy covariance data) in this relatively young forest, explained by enhanced growth above, but not below the ground (Finzi et al, 2020).…”
Section: T H E Grow I Ng Se a Son I N A C L I M At E C H A Nge Con T ...mentioning
confidence: 99%
“…The legacy effect on tree growth in the subtimberline forest was weakened, probably because warming lengthened the growing period. Under these conditions, trees would use more NSC for radial growth and sustenance in the current year, leaving less for the following year [54]. Modeling based on a remote sensing analysis found that climate warming extends the growing season of boreal forest plants [55].…”
Section: Treeline (1511 M)mentioning
confidence: 99%
“…S2). Phenological extraction based on multiple methods consists of three steps: 1) smoothing and interpolating the NDVI date to obtain the smooth and continuous NDVI daily time series; 2) using the threshold value (0.5 for SOS and 0.2 for EOS) or the maximum rate of change to extract the vegetation phenology from each single method (Reed et al, 1994;White et al, 1997;White et al, 2009;Piao et al, 2006); 3) averaging the phenological results obtained by different extraction methods to reduce uncertainties associated with a single method (Due to the different fitting methods, interpolation methods and threshold settings of different extraction methods) (Fu et al, 2021;Fu et al, 2023).…”
Section: Phenology Dates Extractionmentioning
confidence: 99%